A COMPARATIVE STUDY OF READING STRATEGIES USED BY PROSPECTIVE LANGUAGE TEACHERS - Deregözü, Aysel; Üstün, Bilal (International Online Journal of Education and Teaching, 2021)
The study investigated reading strategies used by prospective foreign language teachers studying at a foreign language department of an education faculty in Turkey. It was explored how these strategies differ in view of the variables such as sex, department, education experience, and proficiency levels. For this aim, the Reading Strategy Use Scale is implemented to prospective foreign language teachers studying at a German and English as a Foreign Language Department at a public university in Turkey. The data was collected from prospective foreign language teachers majoring at two departments (English and German) during the academic year 2020 – 2021. The data were collected and analyzed by using the PASW Statistics 18 program. As the data showed normal distribution, the parametric statistical analyses Independent Samples t-Test and one - way ANOVA were used. The findings revealed that reading strategies used by prospective language teachers differ in terms of sex, but do not differ in terms of the department majored. Regarding education experience there were significant differences in planning and assisting strategies. Sophomores and seniors use more assisting strategies, while preparatory class students use less planning strategies compared to freshmen. Furthermore, prospective foreign language teachers with proficiency levels of C use more reading strategies in the construction category compared to A level. Based on the findings of this study, it can be recommended to provide explicit instruction on reading strategies in language teacher education while considering different preferences.